Chapter An Interview in the Beginning of its History. Changes in the Form of Creating the Literary Genre - Kita, Małgorzata (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
An interview as a form of journalistic genre was created in the first half of 19th century. The authoress is researching how this form was constructed in the first century of its existence. The material used in the article is based on the anthology Press Interviews of All Times by Ch. Silvester. Genre analysis shows that from the beginning interlocutors were people chosen on the basis of having something interesting to say on the subject. From the structural point of view one may say that first interviews had been formed as a dialogue between two people presenting pragmatic quantities: a journalist and a person worth to be published in the newspaper. A form parallel to these were interviews with narrative element, similar to the form of report. The authoress is pointing out the similarities between interview and a report.